1999
DOI: 10.1007/s11746-999-0145-9
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of soybean phospholipids by high‐performance liquid chromatography with an evaporative light‐scattering detector

Abstract: Phosphatidylcholine (PC) and phosphatidylethanolamine (PE) from 23 soybean lines with a wide range of fatty acid compositions were resolved into seven fractions by highperformance liquid chromatography (HPLC). Fraction identities were assigned from fatty acid compositions determined by gas chromatography (GC). A mass detector, i.e., an evaporative light-scattering detector, was used for HPLC quantification. The detector response was a power function of PC and PE concentrations. Various correction methods were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Soybean oil was responsible for the contribution of αlinolenic acid (18:3), which represented about 5.1% of the total FA in the mixture. By taking into account that α-linolenic acid in pure soybean oil is usually 8% (14), it is reasonable to conclude that the shortening studied contained no less than 63% soybean oil. Relatively high homogeneity in the molecular structure of the TAG was observed since C 50 , C 52 , and C 54 combined to make up 88.7% of the total.…”
Section: Resultsmentioning
confidence: 92%
“…Soybean oil was responsible for the contribution of αlinolenic acid (18:3), which represented about 5.1% of the total FA in the mixture. By taking into account that α-linolenic acid in pure soybean oil is usually 8% (14), it is reasonable to conclude that the shortening studied contained no less than 63% soybean oil. Relatively high homogeneity in the molecular structure of the TAG was observed since C 50 , C 52 , and C 54 combined to make up 88.7% of the total.…”
Section: Resultsmentioning
confidence: 92%
“…As far as we are aware, this is the first report of systematic identification and the relative contents of individual molecular species of soy PE. Data available on soy PL species is, in fact, focused on PC [5,7,13,16,21]. The major PE molecular species in egg yolk were identified as (C16:0-C18:1)PE (26.6%) and (C18:0-C18:1)PE (26.5%), followed by (C18:0-C18:2)PE (20.0%) and (C16:0-C18:2)PE (16.7%).…”
Section: Determination Of the Molecular Species Of The Pesmentioning
confidence: 99%
“…Three main classes of PL were identified in soy lecithin: phosphatidylcholine (PC), phosphatidylethanolamine (PE) and phosphatidylinositol (PI). In addition to their technological properties, PL, especially PC, are of great nutritional interest: soy PL are rich in essential fatty acids (FA) such as linoleic and alpha-linolenic acids (Wang, Hammond, Cornette, & Fehr, 1999;Wang, Hammond, & Fehr, 1997) and in choline, a constitutive part of one of the polar heads, which is known to be essential for the synthesis of the neurotransmitter acetylcholine or for protecting liver (Shahidi, 2006). As far as assimilation of nutrients is concerned, several studies (Amate, Gil, & Ramirez, 2001;Lemaitre-Delaunay et al, 1999;Wijendran et al, 2002) showed that PC is a better carrier of polyunsaturated fatty acids (PUFA) than triacylglycerols (TAG).…”
Section: Introductionmentioning
confidence: 99%
“…Two molecular species of PC were selected as models: 1-stearoyl-2-oleoyl-sn-glycero-3-phosphocholine (SOPC) and 1-stearoyl-2-linoleoyl-sn-glycero-3-phosphocholine (SLPC). SLPC was previously identified in soy PC (Wang et al, 1997(Wang et al, , 1999, while SOPC was chosen because of the limited number of oxidation products it would generate due to its single double bond. In this study, only the formation of hydroperoxides and oxidative changes that do not include dimerization and degradation were investigated.…”
Section: Introductionmentioning
confidence: 99%